2021
DOI: 10.18388/abp.2020_5343
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rg3 suppresses ovarian cancer cell proliferation and invasion by inhibiting the expression of lncRNA H19

Abstract: Ovarian cancer (OC) is the most malignant disease of the female reproductive system and accounts for a large proportion of gynecological cancer-related deaths. Emerging evidence has indicated that ginsenoside Rg3, one of the tetracyclic triterpenoid saponins in ginseng, plays crucial roles in regulating cancer progression, yet its role and mechanisms in regulating the proliferation and invasion of OC are still elusive. In this study, the cell viability, proliferation, migration and invasion of OC were assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…The resistance of LC cells to conventional therapy and targeted therapy is attributed to EMT (Raoof et al, 2019), so preventing EMT process has become an important approach for LC treatment (Tulchinsky et al, 2019). A previous research identified that Rg3 downregulates the protein level of N-cadherin, but upregulates that of E-cadherin in ovarian cancer cells (Zhao et al, 2021). Rg3 also reduces the expression of vimentin in human cutaneous squamous cell carcinoma (Zhang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The resistance of LC cells to conventional therapy and targeted therapy is attributed to EMT (Raoof et al, 2019), so preventing EMT process has become an important approach for LC treatment (Tulchinsky et al, 2019). A previous research identified that Rg3 downregulates the protein level of N-cadherin, but upregulates that of E-cadherin in ovarian cancer cells (Zhao et al, 2021). Rg3 also reduces the expression of vimentin in human cutaneous squamous cell carcinoma (Zhang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have examined the effects of Rh2 on different tumor cells and documented that it inhibited cell proliferation, induced apoptosis, and arrested the cell cycle [ 23 , 24 , 25 , 26 ]. Other tetracyclic triterpenoids, such as ginsenoside Rg3 [ 27 ], Rg5 [ 28 ] and compound K [ 29 ], can also inhibit tumor cell proliferation. These results suggested that the tetracyclic triterpene ring of these compounds may be responsible for their anti-tumor function.…”
Section: Discussionmentioning
confidence: 99%
“…62 Also, ginsenoside Rg3, one of the tetracyclic triterpenoid saponins in ginseng, reduced the Warburg effect in ovarian cancer cells 66 as well as the proliferation and invasion of the cells via the downregulation of H19. 65,66 These reports indicate that H19 is a potential therapeutic target for treating ovarian cancers.…”
Section: Lncrna H19 In Ovarian Cancermentioning
confidence: 98%
“…64 Also, the knockdown inhibited the proliferation and invasion of ovarian cancer cells, with evidence of E-cadherin upregulation and N-cadherin downregulation in the cells. 65 Additionally, a reduction of H19 expression in a subcutaneous nude mice model of ovarian cancer resulted in the inhibition of tumor growth 53 while H19 suppression reduced glucose consumption and lactate production in ovarian cancer cells. 66 Pyruvate kinase muscle isozyme M2 (PKM2), which is known to promote cellular glucose uptake, lactate production, and cancer metastasis, 67 was also downregulated in the H19-depleted cells via the upregulation of miR-324-5p.…”
Section: Lncrna H19 In Ovarian Cancermentioning
confidence: 99%
See 1 more Smart Citation